Development And Validation Of Simanis Mobile Application For Early Sti Detection Among Adolescents : A Digital Health Promotion And Innovation Study - Nur Hanifah, Astin; Usnawati, Nana; Nuryani, Nuryani; Ayesha Hendriana Ngestiningrum; Ashriady, Ashriady (Politeknik Kesehatan Kemenkes Mamuju, 2025)
The increasing incidence of sexually transmitted infections (STIs) has become more significant among the productive age group. The World Health Organization (WHO) reports that more than one million people are diagnosed with STIs every day, making early detection a crucial step. Preventive efforts include improving knowledge and promoting early detection of STI symptoms; however, many individuals still face difficulties in accessing information related to symptoms, prevention, and treatment. Feelings of shame and the perception that seeking care at health facilities is taboo often result in STI cases being identified at a more advanced stage. Evaluation of health promotion media shows that more than 50% are no longer relevant in the digital era. This study aims to help the public better understand information related to STIs. To develop an Android-based mobile application for the early detection of sexually transmitted infections. This study employed a Research and Development (R&D) design using the 4D model: Define, Design, Develop, and Disseminate. The first year involved evaluating existing health promotion media and identifying strategic issues through focus group discussions (FGDs), followed by application design, expert appraisal, and trials involving 30 respondents. The evaluation revealed that most existing health promotion media were no longer relevant in terms of content, format, and timeliness. The “SIMANIS” mobile application was developed with six main menus: definition, types, symptoms, impacts, transmission, prevention, and self-detection, plus a knowledge questionnaire on STIs. Content validity testing (CVI) by three experts confirmed the application’s validity, while the reliability test yielded a Cronbach’s Alpha value of 0.728. The “SIMANIS” mobile application is valid, reliable, and can be used by adolescents as well as healthcare institutions. The dissemination phase is planned for 2026